HUBUNGAN ANTARA KONSEP DIRI DENGAN INTERAKSI SOSIAL SISWA KELAS VII SMP KESATRIAN 1 SEMARANG - Kaisa Tanazzalul Hikmah; Eka Sari Setianingsih; Farikha Wahyu Lestari (STKIP Subang, 2023)
This research aims to find out about self-concept and social interaction at SMP Kesatrian 1 Semarang. This research was conducted on November 3 2023. Using a quantitative approach, the measuring instruments used were self-concept and social interaction scales. The population used in this research were all class VII students at SMP Kesatrian 1 Semarang. In this research, sampling was carried out using non-probability using a simple random sampling technique. From the calculation results of the two variables, significant results were obtained. Meanwhile, the r table value for a sample size of 52 with a significance level of 5% is 0.273, which means the two variables have a significant relationship. Therefore | r count | 1 | > | r table | 0.273, when compared with the interpretation table, shows that there is a very strong correlation between the variables of self-concept and social interaction. However, these results show that there is a relationship between self-concept and the social interaction of class VII students at Kesatrian 1 Middle School Semarang.